Environmental distribution of Cryptococcus neoformans and C. gattii around the Mediterranean basin - ÇERİKÇİOĞLU, NİLGÜN (OXFORD UNIV PRESS, 2016)
In order to elucidate the distribution of Cryptococcus neoformans and C. gattii in the Mediterranean basin, an extensive environmental survey was carried out during 2012-2015. A total of 302 sites located in 12 countries were sampled, 6436 samples from 3765 trees were collected and 5% of trees were found to be colonized by cryptococcal yeasts. Cryptococcus neoformans was isolated from 177 trees and C. gattii from 13. Cryptococcus neoformans colonized 27% of Ceratonia, 10% of Olea, Platanus and Prunus trees and a lower percentage of other tree genera. The 13 C. gattii isolates were collected from five Eucalyptus, four Ceratonia, two Pinus and two Olea trees. Cryptococcus neoformans was distributed all around the Mediterranean basin, whereas C. gattii was isolated in Greece, Southern Italy and Spain, in agreement with previous findings from both clinical and environmental sources. Among C. neoformans isolates, VNI was the prevalent molecular type but VNII, VNIV and VNIII hybrid strains were also isolated. With the exception of a single VGIV isolate, all C. gattii isolates were VGI. The results confirmed the presence of both Cryptococcus species in the Mediterranean environment, and showed that both carob and olive trees represent an important niche for these yeasts.
Keywords: Cryptococcus; C. neoformans; C. gattii; environment; Europe; epidemiology; molecular typing; VAR. GATTII; IMMUNOCOMPETENT PATIENT; GENETIC DIVERSITY; BRITISH-COLUMBIA; SPECIES COMPLEX; MATING-TYPES; SEROTYPE-D; STRAINS; MENINGITIS; INFECTION